Artificial intelligence - Thomas, Peggy 1960- (Lucent library of science and technology, 2005)
A factbook on the development and uses of intelligent robots that utilize artificial intelligence. An overview of how researchers simulate brain processes in these machines, and the variety of uses the machines/robots have. Written for young adults.